Equality of opportunity in Irish schools - a reassessment - Whelan, Christopher T.; Whelan, Brendan J. (Economic & Social Studies, 1985)
In a recent publication, we examined the available evidence on social mobility in the Republic of Ireland. Our contention that substantial inequalities exist conflicts sharply with the conclusion of Greaney and Kellaghan `that the meritocratic ideal is at least being approached? in Irish second-level schools. In this paper we attempt to show that Greaney and Kellaghan have ignored substantial inequalities in their own data. Our criticisms centre on three major issues, (i) We contend that their measure of class is deficient in that it fails to distinguish adequately between manual and non-manual occupations and to distinguish occupations by employment status, (ii) Greaney and Kellaghan do not provide any formal statistical test of meritocracy. We define and test an appropriate model (based on their published data) which establishes the existence of substantial inequalities. Quoting research from other sources, we suggest that the importance of ability/gender interactions has been underestimated. The class-based inequalities in transition probabilities derived from our model increase as the students progress through the educational system. (iii) We believe that Greaney and Kellaghan fail to examine systematically the sources and consequences of ability differences. In particular, we draw attention to other research which emphasises the importance of family background in determining ability and related variables.
Keywords: Social mobility; Educational equality